Towards Standardized Hydration Testing Protocols for Natural Product-Based Nanoemulgel Moisturizers: A Systematic Review - Iskandar, Benni; Eka Saputri Nst, Sandry; Inggrid. P, Debora; Ami Sari, Rosi; Pulpa Susila, Afriani (Indonesian Journal of Pharmaceutics, 2024)
The growing complexity of moisturizer formulations, particularly those incorporating natural product-based nanoemulgels, highlights an urgent need for standardized efficacy evaluation methods. This systematic review critically examines hydration testing methodologies used for natural ingredient-based nanoemulgel moisturizers, with a focus on their validity, reliability, and practical application. Through a comprehensive analysis of 32 peer-reviewed articles published between 2000 and 2023, this study identified several key limitations in current practices, including inconsistent testing conditions, the absence of standardized protocols for assessing natural ingredients, and variability in reporting methods. The findings emphasize the necessity of developing robust, standardized hydration testing protocols tailored specifically for natural product-based nanoemulgels. By addressing these challenges, this study lays the groundwork for optimizing nanoemulgel formulations, ensuring reliable efficacy assessments, and enhancing consumer trust in natural-based skincare products. Keyword: Moisturizer, Nanoemulgel, Natural Product